REVITALIZING MALAYSIA'S TOURISM INDUSTRY: STRATEGIES, CHALLENGES, AND THE ROLE OF DIGITAL TRANSFORMATION IN PROMOTING ECOTOURISM - Cai Fa Da; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2024)
Malaysia's tourism industry has historically contributed to GDP and foreign exchange. However, the COVID-19 pandemic devastated the sector, causing record-low visitor arrivals and spending. In response, Malaysia undertook several policies to revitalise the sector. Such plans include the National Tourism Policy 2020–2030, stimulus packages, and infrastructure tax incentives. After the pandemic was contained, widespread vaccinations and innovative transportation strategies like the Vaccination Travel Track helped businesses recover. Malaysia's tourism industry is strategic due to its diverse local and foreign visitors. In 2020, the pandemic drastically reduced international tourism. Domestic tourism was hampered while appearing normal. The hospitality business, costly hotels, grew thanks to government investments. The hotel business suffered a sharp decline in guests and occupancy due to Airbnb's popularity. This study examines Malaysia's tourist sector's issues and its innovative use of the Internet Plus platform to promote ecotourism. The crucial factors were Internet adoption, consumer preferences, trust and security, pricing strategy, mobile apps, and AI Malaysian Tourism Accounting Policy and Practice. It was found that five primary elements affect Malaysia's tourism accounting management. The findings highlight the growing importance of digital transformation and how trust, pricing, and technology shape consumer experiences.